Droplet impingement of heated patterned surface - Tay, Cher Ling (Nanyang Technological University, 2020)
Droplet impaction can be found in nature and industrial application, further study on the droplet train on the heated pattern surface can help our further understanding the phenomena and assistant the application. In this report, two types of pattered surface with different wettability have been investigated experimentally. These two surfaces are 2-faced surface and 4-faced surface. The hydrodynamic of droplet impinging onto these two surfaces has been revealed by the high-speed camera. The droplet releasing heights were controlled at the various heights. By analyzing the experimental results, we have found. As the releasing droplet from 10mm height to 2-faced surface, the droplet rebounded when the surface temperature reached 270℃. Since the right-hand side surface is hydrophilic, the droplet tended to incline to the right side slightly. As the releasing droplet increases to 20mm height to 2-faced surface, the prompt splashing begins when the surface temperature reaches 200℃. The amount of the droplet inclination is decreasing as the surface temperature increasing. When the surface temperature increased from 280℃ to 310℃, the droplet had the tendency to rebound, but the bottom of the droplet still attaches on the surface. When the surface temperature increased to 320℃, the whole droplet rebounds totally from the surface. However. the releasing droplet was at 40mm height to 4-faced surface, when the weber number is much more tendency to remain in the centre due to the surface balancing out the forces. When releasing droplet from 80mm and 120mm height to 4-faced hybrid specimen, the droplet showed to incline to the hydrophilic surface. It was observed when the it shows the increase in rebound as the height of the droplet increases it had tend to have a higher spread when the droplet impinged on the surface this is due to having a higher weber number ergo higher kinetic energy. The future suggestions are given on the experiments at the end of report.